The effectiveness of using dry and wet cupping therapy to get rid of Osteo prominent in the lower heel of the Down syndrome class - Haidar, Alaa Khalaf; Mahmoud, Ahmed Shaker; Khalifa, Suzan; Saad Ahmed, Judy Omar (International Journal of Psychosocial Rehabilitation, 2020)
Cupping therapy is an essential treating method for healthy and non-healthy humans. Wet and dry cupping played a vital role in sports activities. In this research, the researcher used dry and wet therapy to treat Osteo prominent problems in the foot heel of the down syndrome category. The researcher used the experimental approach which suites the research requirements. The category of the research was a ten down syndrome volunteers who don’t have chronic diseases. The research results to prove the effect of dry and wet cupping which had a positive effect on some Physiological variables; body mass, pulse rate, diastolic systolic blood pressure. Another foundation of the research was the use of dry and wet cupping that proves a positive effect on the decomposition of sediments in the heel due to excess weight in the down syndrome category. The improvements caused a raising in the health fitness of the research sample.